Nitration-Oximization of Styrene Derivatives with tert-Butyl Nitrite: Synthesis of α-Nitrooximes - Napasawan Chumnanvej (2018)
Copyright © 2016 SIOC, CAS, Shanghai & WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A highly efficient method for direct nitration-oximization of styrene derivatives using tert-butyl nitrite (t-BuONO) in DMSO was developed. The present method offers a convenient and practical approach for the synthesis of α-nitrooximes in moderate to high yields. The salient features entail mild reaction conditions, metal-free reagent, environmentally benign solvent and simple experimental procedure.